Interiors in the Polish feature film of the 1960s as a source of knowledge and a reference point for contemporary architectural designs - Gawlak, Agata; Matuszewska, Magda (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The aim of the article is to draw attention to the relationship between the 1960's design trends, based on the example of the Polish film, and contemporary trends in furniture design. The reference to films of the 1960s as one of the crucial sources of knowledge about the interiors of that period is to be a pretext for further discussion on the timelessness of the 1960s designs, taking into consideration the particular political context in the Polish People's Republic. The article, moreover, aims to show how film sources, analysed by architects, can be used in other disciplines of science, within the framework of interdisciplinary research. Summing up, the feature film is an important supplementary source of knowledge about architectural forms and interiors.